PEMBELAJARAN MENULIS TEKS ULASAN PADA SISWA KELAS VIII - Almuharram, Ibnu Thalif; Syambasril, Syambasril; Ramdani, Deden (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract This research was motivated the MTsN 2 school in Pontianak city was one of the schools that used K13, curriculum carried out the activities of implementing students to become more active. Thus, a follow-up to documenting the school is deemed necessary, because it can be an example and reference to prospective teachers and teachers who have taught in schools. This study aims to describe the lesson plan, implementation, and resultsÂ for writing text reviews on class VIII MTsN 2 Pontianak City 2018/2019. The results of (1) Learning Implementation Plans (LIP) designed by the teacher are in accordance with the LIP component. Viewed from several aspects the teacher has included the components made in accordance with the format of the Minister of Education and Culture No. 22 of 2016. (2) The implementation has referred to the LIP made, namely from the preliminary activities, core activities, and closing activities. The learning process uses a scientific approach and the learning method used is the Descovery Learning method. (3) The results of the acquisition of students for the implementation of the learning that has been carried out have been quite good.Keywords: Review Text, Teaching Learning